2015
DOI: 10.1007/s10753-015-0272-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Astragaloside IV Against Paraquat-Induced Lung Injury in Mice by Suppressing Rho Signaling

Abstract: The purpose of the present study was to evaluate the protective effects of astragaloside IV (AS IV) against paraquat (PQ)-induced pulmonary injury in vivo. Fifty BALB/C mice were randomized into five groups: (1) control, (2) PQ, (3) PQ + dexamethasone (Dex, 5 mg/kg), (4) PQ + AS IV (50 mg/kg), and (5) PQ + AS IV (100 mg/kg). A single dose of PQ (50 mg/kg, i.p.) was intraperitoneally given to induced acute lung injury. Then, mice were treated with AS IV (50 and 100 mg/kg/day, orally) for 5 days. At the end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(65 citation statements)
references
References 42 publications
4
57
0
Order By: Relevance
“…The acquired data suggested that smoke stimulation increased the expressions of RhoA, ROCK1 and ROCK2, while fasudil dramatically reversed these alterations. As the downstream target of ROCK, NF-κB signaling has been widely reported to be involved in inflammatory responses [21]. Our results further demonstrated that NF-κB signaling was significantly activated in smoke-exposed mice.…”
Section: Discussionsupporting
confidence: 79%
“…The acquired data suggested that smoke stimulation increased the expressions of RhoA, ROCK1 and ROCK2, while fasudil dramatically reversed these alterations. As the downstream target of ROCK, NF-κB signaling has been widely reported to be involved in inflammatory responses [21]. Our results further demonstrated that NF-κB signaling was significantly activated in smoke-exposed mice.…”
Section: Discussionsupporting
confidence: 79%
“…Previous evidence found NDEA exposure results in high MDA formation [22]. Lipid peroxidation is one of most extensively studied manifestations of oxygen toxicity [23]. As a byproduct of lipid peroxidation, MDA is generated under oxidative stress and considered as reliable index for oxidative damage which attributed to the plasma membrane and the resultant production [24].…”
Section: Discussionmentioning
confidence: 99%
“…Respectively, TNF α is implicated in acute phase of inflammation by activating epithelial cells and subsequent conducing to the generation of other inflammatory mediators [57]. As an important modular in the upper reaches of the immune response, IL1 β participates in epithelial repair and amplifies the inflammatory cascade [16].…”
Section: Discussionmentioning
confidence: 99%